2017
DOI: 10.15252/embr.201643309
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial E3 ligase MARCH 5 regulates FUNDC 1 to fine‐tune hypoxic mitophagy

Abstract: Mitophagy is an essential process for mitochondrial quality control and turnover. It is activated by two distinct pathways, one dependent on ubiquitin and the other dependent on receptors including FUNDC1. It is not clear whether these pathways coordinate to mediate mitophagy in response to stresses, or how mitophagy receptors sense stress signals to activate mitophagy. We find that the mitochondrial E3 ligase MARCH5, but not Parkin, plays a role in regulating hypoxia-induced mitophagy by ubiquitylating and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
153
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(164 citation statements)
references
References 56 publications
11
153
0
Order By: Relevance
“…This process accelerates Parkin translocation from the cytosol to the mitochondria,49, 54 and thus ubiquitinates mitochondrial outer membrane proteins to promote recruitment of an autophagosome 55. Other than the PINK1/Parkin pathway, BNIP3, BNIP3L and FUNDC1 are also emerging key players in the regulation of mitophagy 13, 56, 57. A full understanding of the regulatory mechanisms involved in cardiomyocyte mitophagy has yet to be developed, as well as their connection with the onset of diabetes 13.…”
Section: Discussionmentioning
confidence: 99%
“…This process accelerates Parkin translocation from the cytosol to the mitochondria,49, 54 and thus ubiquitinates mitochondrial outer membrane proteins to promote recruitment of an autophagosome 55. Other than the PINK1/Parkin pathway, BNIP3, BNIP3L and FUNDC1 are also emerging key players in the regulation of mitophagy 13, 56, 57. A full understanding of the regulatory mechanisms involved in cardiomyocyte mitophagy has yet to be developed, as well as their connection with the onset of diabetes 13.…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxia condition, ULK1‐mediated phosphorylation at Ser17 can promote the interaction between FUNDC1 and LC3 . Additionally, the mitochondrial E3 ligase MARCH5 can regulate hypoxia‐induced mitophagy through ubiquitinating and degrading FUNDC1 . The receptor‐interacting serine/threonine‐protein kinase 3 (Ripk3) can suppress FUNDC1‐mediated mitophagy and promote mitochondrial apoptosis in cardiac ischemia/reperfusion injury .…”
Section: Mitophagy In Mammalsmentioning
confidence: 99%
“…47 Additionally, the mitochondrial E3 ligase MARCH5 can regulate hypoxia-induced mitophagy through ubiquitinating and degrading FUNDC1. 48 The receptor-interacting serine/threonine-protein kinase 3 (Ripk3) can suppress FUNDC1-mediated mitophagy and promote mitochondrial apoptosis in cardiac ischemia/reperfusion injury. 49 Unexpectedly, it is also suggested that knockdown or overexpression of FUNDC1 has insignificant influence on starvation-or hypoxia-induced mitophagy.…”
Section: Fundc1-mediated Mitophagymentioning
confidence: 99%
“…The interaction between FUNDC1 and LC3 can be further strengthened following UNC‐51‐like kinase 1 (ULK1)‐dependent phosphorylation of FUNDC1 at serine 17 . Beyond phosphorylation, ubiquitylation has also been implicated as a FUNDC1 control mechanism . The OMM‐localised E3 ligase MARCH5 can ubiquitylate FUNDC1 at the early stages of hypoxia, before FUNDC1 dephosphorylation, to prevent excessive mitophagy .…”
Section: Mechanistic Basics For Mitophagy Initiationmentioning
confidence: 99%
“…Beyond phosphorylation, ubiquitylation has also been implicated as a FUNDC1 control mechanism . The OMM‐localised E3 ligase MARCH5 can ubiquitylate FUNDC1 at the early stages of hypoxia, before FUNDC1 dephosphorylation, to prevent excessive mitophagy .…”
Section: Mechanistic Basics For Mitophagy Initiationmentioning
confidence: 99%